PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA EKSPRES KILAT DI KOTA PASURUAN - Fadiba, Fara; Sutikno, Bambang; Erwantiningsih, Eni (Bhinneka Multidisiplin Journal, 2025)
The high job demands in the e-commerce logistics industry, particularly among couriers at PT. Nusantara Ekspres Kilat (NEK) in Pasuruan City, have the potential to affect employee performance through workload and work stress. This study aims to analyze the simultaneous and partial effects of workload and work stress on courier performance. Data were collected using a Likert-scale questionnaire distributed to 65 couriers selected through purposive sampling and analyzed using multiple linear regression with SPSS. The results show that workload and work stress simultaneously have a significant effect on performance (sig. value = 0.000 < 0.05; F calculated = 222.491 > F table = 1.998). Partially, workload has a positive effect (β = 1.512; sig. = 0.000) and work stress also has a positive effect (β = 0.456; sig. = 0.000). The coefficient of determination (Adjusted R²) of 0.878 indicates that 87.8% of the variation in performance is explained by the two variables. These findings confirm that while workload and work stress can enhance performance, optimal management of both is necessary to minimize potential negative impacts.